Pengaruh Pembelajaran Antropolinguistik Terhadap Optimalisasi Kompetensi Perawat di Ruang Rawat Inap RSUD H. Sahudin Kutacane - Yusnaini Yusnaini; Dina Andriani Br Karo; Devi Annisa Marpaung; Mariza Elvira (Malahayati Nursing Journal, 2024)
ABSTRACT Globalization trends increase human mobility and cultural exchange between countries is proliferating in society including the health care environment. Low nurse competency can limit the provision of professional nursing care to patients. can lead to misinterpretation of patient needs, inaccurate diagnoses, and treatment errors. Competent nurses can provide culturally aware, safe, and equitable nursing care. Anthropolinguistic learning support is a way to facilitate cultural and linguistic understanding within the scope of nursing practice. This research aims to analyze the effectiveness of anthropolinguistic learning in developing nurse competency in the Inpatient Room at H. Sahudin Kutacane Kutacane Hospital. The design of this research is a quasi-experiment with pre and post-tests without control. The population in this study were all nurses in the inpatient room at H. Sahudin Kutacane Kutacane Hospital, totaling 146 nurses using a sampling technique, namely total sampling. Data were analyzed using the Wilcoxon signed-rank test. The research results showed that there was a difference between the average pre-test score for developing nurse competency (55.2) and the average post-test score for developing nurse competency (74.1) and there was an influence of the implementation of anthropolinguistic learning on the development of nurse competency with Asymp scores. Sig (2-tailed) 0.021. This research concludes that the implementation of anthropolinguistic learning has the opportunity to support the development of nurse competency. So, it is hoped that hospital management will facilitate routine and ongoing training in implementing anthropolinguistics for nurses. Keywords: Anthropolinguistics, Language, Culture, Competence, Nurse  ABSTRAK Tren globalisasi meningkatkan mobilitas manusia dan pertukaran budaya antar negara berkembang pesat di masyarakat termasuk lingkungan perawatan kesehatan. Kompetensi perawat yang rendah dapat membatasi pemberian asuhan keperawatan yang professional bagi pasien. dapat menyebabkan salah tafsir kebutuhan pasien, diagnosa yang tidak akurat dan kesalahan pengobatan. Perawat yang berkompeten dapat memberikan asuhan keperawatan yang sadar budaya, aman, dan adil untuk semua. Dukungan pembelajaran antropolinguistik merupakan suatu cara memfasilitasi pemahaman budaya dan bahasa dalam lingkup praktik keperawatan. Penelitian ini bertujuan menganalisis efektivitas pembelajaran antropolinguistik terhadap pengembangan kompetensi perawat di Ruang Rawat Inap RSUD H. Sahudin Kutacane Kutacane. Desain penelitian ini adalah quasi experiment dengan pre and post test without control. Populasi dalam penelitian ini adalah seluruh perawat di ruang rawat inap RSUD H. Sahudin Kutacane Kutacane yang berjumlah 146 perawat dengan teknik pengambilan sampel yaitu total sampling. Data dianalisis menggunakan uji wilcoxon signed rangk test. Hasil penelitian didapatkan bahwa ada perbedaan rata-rata skor pre-test pengembangan kompetensi perawat (55,2) dengan rata-rata post-test pengembangan kompetensi perawat (74,1) serta ada pengaruh implementasi pembelajaran antropolinguistik terhadap pengembangan kompetensi perawat dengan nilai Asymp.Sig (2-tailed) 0,021. Kesimpulan penelitian ini adalah implementasi pembelajaran antropolinguistik berpeluang mendukung pengembangan kompetensi perawat. Jadi, diharapkan pihak manajerial rumah sakit memfasilitasi pelatihan rutin dan berkelanjutan dalam implementasi antropolinguistik bagi perawat. Kata Kunci: Antropolinguistik, Bahasa, Budaya, Kompetensi, Perawat